Evaluating methods of application of biocontrol agent in the control of mungbean root rot - and R. SAMIAPPAN, T. RAGUCHANDER, K. RAJAPPAN (Indian Phytopathology, 2002)
During the kharif season of 1991, field trials were conducted at the National Pulses Research Centre, Vamban, Tamil Nadu, India, to determine the efficacy of seed pelleting and row application of Trichoderma harzianum and T. viride (isolates I, II and III) on the control of dry root rot (caused by Macrophomina phaseolina) of mungbean (Vigna radiata cv. Co3). M. phaseolina infection was reduced by seed pelleting with Trichoderma viride isolates, with talc used as the carrier. Among the isolates, T.viride-III supported higher plant growth, better native Rhizobium nodulation and grain yield. Sclerotial number and root rot incidence were greatly reduced with seed pelleting of antagonists as compared to row application. Rhizosphere soil from the seedpelleting treatment had a higher number of Trichoderma chlamydospores.